ALA?KARA DALAM KAKAWIN HAÑANG NIRARTHA : KAJIAN STILISTIKA - Istri Agung Dharmayanti, Ida Ayu (Humanis, 2015)
Kakawin Hañang Nirartha tells about the love story of Nirartha. The text of Kakawin Hañang Nirartha gives the views of the Nirartha’s love to his couple through the faith that he shows in his daily activities which should be followed by a person in the form of faith in action, in speech, and in thought. The author’s ability in using figurative speech makes this literary work worth to be analyzed. This research was aimed to analyze the formal and narrative structure of the Kakawin Hañang Nirartha. The formal structure of Kakawin Hañang Nirartha are guru-laghu, wrêta, m?tra, ga?a, canda, carik, pada, pupuh and ala?kara. The narrative structure of Kakawin Hañang Nirartha are manggala, corpus and epilog. The types of Ala?kara used in the Kakawin Hañang Nirartha are (1) Sabd?la?kara, in the form of yamaka and anuprasa, (2) Arth?la?kara which is in the form of rupaka, rupakabhyadika, wyatireka and warta. And (3) pujasmara, it is the smallest form of metaphor of Kakawin Hañang Nirartha which is aimed to attract the Bhatara Smara comes to the author’s thought.
Keywords: kakawin, alamkara, and pusjasmara